The Partially Clothed Emperor: Evidence-Based Practices - Taxman, Faye S. (Journal of contemporary criminal justice, 2018)
The evidence-based practices literature has defined a core set of practices and treatments that are effective, at least in empirical studies. Implementing these evidence-based practices and treatments requires a different set of empirical studies to understand the operational issues that affects client-driven outcomes. In this article, we review the following three areas: (a) use of a standardized risk and need assessment tool, (b) use of cognitive-behavioral programs to address criminogenic needs, and (c) use of swift and certain responses to shape behavior. The review focuses on the unanswered questions regarding implementation and organizational change strategies to increase receptivity for the evidence-based practices, lay the foundation for improving effectiveness of “evidence-based practices and treatments,” and provide a work environment that supports evidence-based practices and treatments. This article outlines a research agenda to build implementation knowledge that can further the use of evidence-based practices and treatments.